PENGARUH POLITIK HUKUM TERHADAP PENGHINAAN DAN ATAU PENCEMARAN NAMA BAIK BERDASARKAN UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Raihana; Ermanto; Cecep Sujapar (Collegium Studiosum Journal, 2022)
Regulating the offense of insult or defamation contained in Article 27 paragraph (3) of the ITE Law does not simply accommodate or become the best way out in resolving defamation offenses committed using online media. Article 27 paragraph (3) of the ITE Law reads: Everyone intentionally and without rights distributes and/or transmits and/or makes accessible Electronic Information and/or Electronic Documents that contain insulting content or defamation. Based on the article above, in terms of the implementation of the proof against the article, you have to be really careful, so that this does not become a loophole for arrogant parties to make this article a rubber article. The method used is normative legal research. Based on the results of the study it is known that the influence of legal politics on insults and/or defamation based on the Information and Electronic Transactions Law that during the discussion process related to the formation of the ITE Law in the DPR RI was carried out by the Special Committee on the ITE RUU ITE DPR RI with the parties involved. related to the formation of this Law, no consideration was found regarding the need to formulate provisions regarding insult and/or defamation which are currently contained in Article 27 paragraph (3) of Law Number 11 of 2008 concerning Information and Electronic Transactions.